2014
DOI: 10.1016/j.regg.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Guía de consenso para el abordaje de la neumonía adquirida en la comunidad en el paciente anciano

Abstract: The incidence of community-acquired pneumonia increases with age and is associated with an elevated morbidity and mortality due to the physiological changes associated with aging and a greater presence of chronic disease. Taking into account the importance of this disease from an epidemiological and prognostic point of view, and the enormous heterogeneity described in the clinical management of the elderly, we believe a specific consensus document regarding this patient profile is necessary. The purpose of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
23

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 104 publications
0
13
1
23
Order By: Relevance
“…Although there are no specific studies on this population, it is generally assumed that there are no significant differences between the management of older and younger patients with the same characteristics [18]. In this study, however, we found that older patients have higher 30-day mortality.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Although there are no specific studies on this population, it is generally assumed that there are no significant differences between the management of older and younger patients with the same characteristics [18]. In this study, however, we found that older patients have higher 30-day mortality.…”
Section: Discussioncontrasting
confidence: 67%
“…As a consequence, it has recently been proposed that diagnostic and therapeutic decisions should be based more on the patients’ degree of frailty than their age [18, 19]. This concept may be a better reflection of biological than chronological age.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52] CPGs that included pneumonia associated with health care, 53,54 audit, 55 note, 56 summary and comment, 57 "Consensus statements", [58][59][60][61][62] reviews, [63][64][65] includes various types of infections not only pneumonia, 66,67 description of adaptation of a CPG, 68 newsletter, 69 very little information available, 70 updated guidelines, [71][72][73] could not be downloaded the full version, 74 and there was a special case of a CPG published in different journals in the same year and it was excluded because it was a consensus on the two different publications. 58,59 About the 18 CPGs selected: there is an American guideline (IDSA), 34 one is from Brazil, 33 one from Italy (Gulf), 22 one from India, 27 two European (ERS and Multidisciplinary), 20,28 two from Spain (SEPAR and Andalusian), 21,31 a Peruvian guideline, 23 a Dutch guideline (SWAB), 29 two British guidelines (NICE and BTS), 17,32 a Lebanese guideline, 18 one from Latin America (Consensur), 30 one Colombian guideline, 24 one Chinese, 25 one Korean 26 and one Swedish. 19…”
Section: Re Sultsmentioning
confidence: 99%
“…La ausencia de fiebre, hipoxemia o síntomas respiratorios no permiten descartar el diagnóstico de neumonía. 7 Al ser este un grupo poblacional clínicamente muy heterogéneo, ha surgido la necesidad de categorizar al paciente adulto mayor. 7 Un anciano sin criterios de fragilidad es aquel que es independiente para las actividades básicas e instrumentales de la vida diaria, sin comorbilidad significativa, ni otros problemas mentales ni sociales asociados.…”
Section: Categorización Del Adulto Mayor Y Valoración Geriátricaunclassified
“…aparato respiratorio e inmunitario, junto con la mayor probabilidad de situaciones clínicas, sociales y de enfermedades crónicas que van siendo acumulativas con la edad, lo cual convierten al anciano en un sujeto más vulnerable al desarrollo de infecciones, más específicamente de la neumonía, así como de riesgo incrementado de un peor resultado de las misma. 2,4,7,8…”
unclassified